Synergic use of botulinum toxin injection and radial extracorporeal shockwave therapy in Multiple Sclerosis spasticity. - Marinaro, Cinzia; Costantino, Cosimo; d'Esposito, Oriana; Barletta, Marianna; Indino, Angelo; de Scorpio, Gerardo; Ammendolia, Antonio (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: In Multiple Sclerosis (MS) spasticity worsen patient’s quality of life. Botulinum NeuroToxin TypeA (BoNT-A) is extensively used in focal spasticity, frequently combined with physical therapies. Radial extracorporeal shock waves (rESW) were already used in association with BoNT-A. Considering that loss of efficacy and adverse events are determinants of BoNT-A treatment interruption, this study aimed to evaluate the possibility to prolong BoNT-A’s effect by using rESW in MS focal spasticity. Methods: Sixteen MS patients with spasticity of triceps surae muscles were first subjected to BoNT-A therapy and, four months later, to 4 sections of rESWT. Patients were evaluated before, 30, 90 days after the end of the treatments, by using Modified Ashworth Scale (MAS), Modified Tardieu Scale (MTS) and kinematic analysis of passive and active ankle ROM. Results: BoNT-A determined a significant reduction of spasticity evaluated by MAS with a reduction of positive effects after 4months (p<0.05); MTS highlighted the efficacy only 90 days after injection (p<0.05). rESWT decreased MAS values at the end and 30 days later the treatment (p<0.01); MTS values showed instead a prolonged effect (p<0.01). BoNT-A determined a gain of passive and active ankle ROM, persisting along with treatment and peaking the maximum value after rESWT (p<0.05). Conclusions: rESWT can prolong BoNT-A effect inducing significant reduction of spasticity and improvement in passive and active ankle ROM in MS patients. The use of rESWT following BoNT-A injection is useful to avoid some limitations and to prolong the therapeutic effects of BoNT-A therapy.